The quantitative and qulitative analysis of knowledge production in physical education: the northest brazilian experience - Sánchez Gamboa, Silvio; Chaves-Gamboa, Márcia (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The controversy between analytic and interpretative epistemology is presenting into the research about knowledge production and these are expressed in the analysis of methods, which are used in scientific research. The thematic project: KNOWLEDGE PRODUCTION IN PHYSICAL EDUCATION entitled: postgraduate impact south and southeast of Brazil, in the formation and the production of magister and phd who work in high schools in the northeast region. It is financial by Amparo Foundation to the research of Sao Paulo state (Proc. 2012/50019-7) it is about the relation between quantitative and qualitative methods and underlined: 1) The construction of scientific field of physical education has theoretical and methodological basis on natural science (physic, biology, mechanic) and human and social science (pedagogy, sociology, psychology) but they confront ways of knowledge validity. The first look for preserving the objectivity, they use a mathematical and statistic language, the second one charged of subjectivity. They prefer the interpretation and the polysemy languages, 2) the analysis made with the production of 750 surveys which were prepared by teachers and doctors who work in 126 courses of physical education in nine states in the Northest of Brazil. The analysis shows that the epistemological dualism is overcoming by the checking of the object of knowledge phenomena reveal numerous determinations and dimensions among them as quantitative as qualitative which cannot be separate into the process of knowledge. 3) Over the base of this dialectic united of opposed. The search leaded the dilemma between quantitative and qualitative approach, the construction of quantitative and qualitative indication sign in order to characterize the theoretical and methodology trend. The use of Cenciometria tools (dates analysis) in order to identify the evolution of theories, authors, schools of thought, the research webs. The use of epistemological categories let us to understand the science and technology indicators in the context of social development and its historic transformations of Brazilian society.